ANALISIS SISTEM INFORMASI AKUNTANSI DALAM PEMBERIAN KREDIT PADA KOPPELOG BULOG MANADO - Suwatalbessy, Jessica Brenda; Morasa, Jenny; Tangkuman, Steven (Universitas Sam Ratulangi, 2018)
Accounting information systems are the main formal system in most companies. Accounting information systems have an important role in lending in which companies can see the effectiveness of accounting systems in lending. The aim of the study was to find out how the procedure for granting credit at the Koppelog Bulog Manado. The results showed that the accounting information systems in giving credit to the Koppelog Bulog Manado was quite effective, but it was just that the lack of good quality resourcesÂ in Koppelog Bulog Manado was due to the average level of education of employees who were not very skilled in their field.Keywords : Accounting information systems, Procedure for granting, Credit